ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI FOOT MASSAGE UNTUK MENURUNKAN HIPERTENSI INTRADIALITIK PADA PASIEN HEMODIALISA - Gabriell Regina Solagracia Massie (2023)
Hemodialysis is one of the treatments given to patients with end-stage chronic kidney failure or End Stage Renal Disease (ESRD). Patients with chronic kidney failure undergoing hemodialysis can get one of the complications, such as intradialytic hypertension. This research was conducted with the aim of knowing the effectiveness of foot massage in reducing intradialytic hypertension. This intervention was given to two patients undergoing hemodialysis at the Gatot Soebroto Army Hospital's hemodialysis unit. Foot massage is given three times over a period of 5-10 minutes during the dialysis session. In providing nursing care, evaluation is carried out after completing the foot massage procedure using a sphygmomanometer to measure blood pressure every hour of hemodialysis. The results obtained after carrying out innovation interventions, that foot massage is effective in reducing intradialytic hypertension as evidenced by the results of blood pressure being 175/85 mmHg in the first session, 150/90 mmHg in the second session and 140/80 mmHg in the third session. At the time of post hemodialysis blood pressure to 130/80 mmHg. Foot massage can have a relaxing effect on stiff muscles, resulting in a stable drop in blood pressure and provide comfort to the patient.